Pengaruh Gairaigo Terhadap Lanskap Linguistik di Nishikasai, Tokyo - Sinaga, Jeremia Pandapotan P.; Arfianty, Rani (Jurnal SORA - Pernik Studi Bahasa Asing, 2024)
Linguistic landscape (LL) refers to the signs of linguistic objects located in public spaces as a place for human social interaction to perform a series of cultural activities. The linguistic landscape in Japan, in particular, on Nishikasai street, Tokyo, uses an absorption word called Gairaigo. This research focuses on the use of Gairaigo in the Japanese linguistic landscape, particularly in Nishikasai street, Tokyo. Through a qualitative method, the research data is drawn from the linguistic landscape along Nishikasai street, Tokyo. In the linguistic landscape of Nishikasai street, Tokyo, there are lexical semantic meanings connected with Gairaigo and there are shifts in the mention and selection of words even though the meaning and function are similar. On the other hand, the absorption of foreign language into Japanese was also found to have no change in word composition or meaning and function. The results of LL's research in Nishikasai, Tokyo showed that the criteria for the formation and use of gairaigo is based on the nuances of meaning contained in the foreign word cannot be represented by an equivalent word in Japanese; the foreign word used as Gairaigo is considered effective and efficient; and the foreign word, according to the sense of language, is considered to have good taste value, good, and harmonious as expressed by Sudjianto (2004).